The Effect of Management Accounting Information Systems on Managerial Performance: Work Stress Level as a Moderating Variable - Rian Suhaeli, Asep (Publikasi Indonesia, 2025)
PT Dizamatra Powerindo is a prominent player in Indonesia's coal mining industry, yet its managerial performance remains suboptimal. This study aims to examine the moderating role of work stress levels in weakening the relationship between management accounting information systems and managerial performance. The research involved 87 managers within the company, with 71 valid responses collected and analyzed using questionnaires. The findings reveal that managerial performance is influenced by management accounting information systems, while the interaction between these systems and work stress levels does not have a direct effect on managerial performance. Furthermore, the study concludes that work stress levels do not moderate the relationship between management accounting information systems and managerial performance.